Factors Influencing The Stock Price of Nepalese Commercial Banks - Gyawali, Bindu (Patan Prospective Journal, 2022)
The purpose of this research is to examine the impact of factors influencing the stock price of Nepalese commercial banks. This research uses MPS as the dependent variable and independent variables are DPS, EPS, P/E ratio, ROA, GDP, and inflation rate. The secondary data has been collected from the annual reports of selected commercial banks for five year study period from 2017 to 2021. Descriptive and causal-comparative research design has been used to analyze and interpret this data using SPSS 23 version. Ten commercial banks are taken as a sample out of 27 banks. The convenience sampling method is used. Multiple linear regression models have been used to show the impact of independent variables on the dependent variable. The result shows that there is a positive and statistically significant effect of DPS, EPS, and P/E ratio on the stock price. ROA and GDP have a positive but not significant effect on the stock price but the inflation rate has a negative and insignificant impact on the stock price.